2017
DOI: 10.22159/ijpps.2017v9i11.20469
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Pyrazole Hybrids as Antitubercular Agents: Synthesis, Biological Evaluation and Molecular Docking Study

Abstract: Objective: Synthesis of new 1, 3-diphenyl pyrazole derivatives 9(a-f) and 10(a-f) using molecular hybridization approach and evaluation of their antitubercular and cytotoxic studies. Methods:The structures of synthesized compounds were confirmed by 1 H NMR, 13 C NMR and mass spectra. The antitubercular activity of compounds and standard drugs were assessed against Mycobacterium tuberculosis using Microplate alamar blue assay (MABA). The cytotoxic activities were performed by Sulforhodamine B (SRB) assay. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The molecular docking results of α-mangosteen to iNOS, COX-1, and COX-2 receptors were directly proportional to previous studies, such as Mohan (2018) [25]. The research reported that two xanthones compounds, namely α-mangosteen and γ-mangosteen isolated from the pericarp of G. mangostana significantly inhibited the production of nitric oxide and PGE2 from RAW cells 246,7 and stimulated lipopolysaccharide (LPS) [15]. The visualization of the molecular docking of the test compound of α-mangosteen can be seen in fig.…”
Section: Tyr341supporting
confidence: 71%
See 2 more Smart Citations
“…The molecular docking results of α-mangosteen to iNOS, COX-1, and COX-2 receptors were directly proportional to previous studies, such as Mohan (2018) [25]. The research reported that two xanthones compounds, namely α-mangosteen and γ-mangosteen isolated from the pericarp of G. mangostana significantly inhibited the production of nitric oxide and PGE2 from RAW cells 246,7 and stimulated lipopolysaccharide (LPS) [15]. The visualization of the molecular docking of the test compound of α-mangosteen can be seen in fig.…”
Section: Tyr341supporting
confidence: 71%
“…The Molecular docking validation was carried out by redocking between the native ligands and the target protein with Autodock 4.4. This validation was valid with the parameter value of RMSD less than 3 Å (Root Mean Square Distance) [15]. For the validation of the moorings carried out on the natural ligand iNOS enzyme, L-arginine was used.…”
Section: Docking Validation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary investigation of the anticancer activity of the newly synthesized pyrazolopyrimidine derivatives was screened in vitro against EAC. The IC 50 values of these molecules were determined (Tables 2-4) [14][15][16][17]. From the data, we concluded that at 100 µg/ml, the higher anticancer activity of molecules 8e and 8g (Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the chemical modification of its molecule in position 7 is accompanied by the production of compounds with a narrower profile of pharmacological action against the background of reducing the number of side effects and low toxicity [3]. Various derivatives of pyrazole are also promising research objects since among them are identified monoamine oxidase and cyclooxygenase-2 inhibitors, substances with hepatoprotective, anti-inflammatory, analgesic, antioxidant, antimicrobial, anti-tuberculosis, and antitumor activities [4][5][6]. Thus, it seemed to us appropriate to combine in the same molecule two abovementioned heterocycles, which could lead to the obtainment of target products with a higher potential for biological activity.…”
Section: Introductionmentioning
confidence: 99%